Narrar a voz: trajetórias de uma voz-experiência em busca da voz própria - Gelamo, Renata Pelloso [UNESP] (2018)
In this thesis, I present questions, reflections, and learnings from narratives, either mine and form other people which whom I met during the trajectories in the search for the self-voice and that led me to the creation of the “Voice Atelier”, a project built in the borderline of different fields of knowledge which hold the voice as its interest. The textual structure I propose for this thesis shows the creation and sustaining of a space where I could name, in first person, the processes I lived during my own history with the voice. I narrate moments of impoverishment of the experience, passing through the silencing of my own voice, submitted to what others had to say, or about what the renowned scientific fields had to say about the voice, as well as the experience of collapse lived through the contact wit the voices of the working songs of the Destaladeiras de Fumo (Workers who manually struke tobacco leafs) from Arapiraca, when I suspended all the truths I knew by then about the voice. At last, I narrate how the “Voice Atelier” happens, an opens space for invention of a voice-experience, a voice that can listen and be listened, can narrate its own history, inhabits its own body and, exposes, looks after and is aware of itself. Through this pathway of the voice-experience we reach the self-voice: A voice capable of self-enunciating and self-inventing.